2014
DOI: 10.1042/bj20140372
|View full text |Cite
|
Sign up to set email alerts
|

Lysine methylation is an endogenous post-translational modification of tau protein in human brain and a modulator of aggregation propensity

Abstract: In Alzheimer disease, the microtubule-associated protein tau dissociates from the neuronal cytoskeleton and aggregates to form cytoplasmic inclusions. Although hyper-phosphorylation of tau Ser and Thr residues is an established trigger of tau misfunction and aggregation, tau modifications extend to Lys residues as well, raising the possibility that different modification signatures depress or promote aggregation propensity depending on site occupancy. To identify Lys-residue modifications associated with norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(138 citation statements)
references
References 72 publications
6
132
0
Order By: Relevance
“…O-GlcNAc modification has been proposed to prevent tau phosphorylation by occupying many serines and threonines [17][18][19] , thereby preventing dissociation of tau from microtubules and tau aggregation. However, only one O-GlcNAc site has been found on endogenous tau 20 , in contrast with 51 phosphorylation sites 14,21 . Ubiquitination of tau has been identified by mass spectrometry of paired helical filaments isolated from AD brains 22,23 .…”
mentioning
confidence: 96%
“…O-GlcNAc modification has been proposed to prevent tau phosphorylation by occupying many serines and threonines [17][18][19] , thereby preventing dissociation of tau from microtubules and tau aggregation. However, only one O-GlcNAc site has been found on endogenous tau 20 , in contrast with 51 phosphorylation sites 14,21 . Ubiquitination of tau has been identified by mass spectrometry of paired helical filaments isolated from AD brains 22,23 .…”
mentioning
confidence: 96%
“…These distinct Tau isoforms/proteoforms are differentially detected in the brain parenchyma of patients and eventually in CSF. Prior studies based on western blotting and ELISA suggested the presence of several Tau fragments and many phosphorylated forms [1,12,13] in this biological fluid. However, the low resolution of these techniques and lack of specific antibodies for its many possible isoforms has so far prevented obtaining a global view on Tau molecular profile in the CSF.…”
Section: Introductionmentioning
confidence: 99%
“…These residues are exposed as Tau is an intrinsically disordered protein subject to modification by numerous kinases (7). Mass spectrometry (MS) analyses have identified ϳ45 phosphorylated sites on Tau aggregates extracted from AD patients with a typical paired helical filament (PHF) morphology (8,9) compared with 15-30 phosphorylation sites in soluble Tau extracted from mice (10) or normal human brain (11). Monoclonal antibodies such as AT8 (recognizing Ser(P)-202/Thr(P)-205; Ref.…”
mentioning
confidence: 99%